“That pulled the rug out from under my feet!” : adverse experiences and altered emotion processing in patients with functional neurological symptoms compared to healthy comparison subjects - Steffen, Astrid; Fiess, Johanna; Schmidt, Roger; Rockstroh, Brigitte (My University, 2015)
Background
Medically unexplained movement or sensibility disorders, recently defined in DSM-5 as functional neurological symptoms (FNS), are still insufficiently understood. Stress and trauma have been addressed as relevant factors in FNS genesis. Altered emotion processing has been discussed.
The present study screened different types and times of adverse experiences in childhood and adulthood in patients with FNS as well as in healthy individuals. The relationship between stress profile, aspects of emotion processing and symptom severity was examined, with the hypothesis that particularly emotional childhood adversities would have an impact on dysfunctional emotion processing as a mediator of FNS.
Methods
Adverse childhood experiences (ACE), recent negative life events (LE), alexithymia, and emotion regulation style were assessed in 45 inpatients diagnosed with dissociative disorder expressing FNS, and in 45 healthy comparison subjects (HC).
Results
Patients reported more severe FNS, more (particularly emotional) ACE, and more LE than HC. FNS severity varied with emotional ACE and negative LE, and LE partially mediated the relation between ACE and FNS. Alexithymia and suppressive emotion regulation style were stronger in patients than HC, and alexithymia varied with FNS severity. Structural equation modeling verified partial mediation of the relationship between emotional ACE and FNS by alexithymia.
Conclusions
Early, emotional and accumulating stress show a substantial impact on FNS-associated emotion processing, influencing FNS. Understanding this complex interplay of stress, emotion processing and the severity of FNS is relevant not only for theoretical models, but, as a consequence also inform diagnostic and therapeutic adjustments.
Keywords: Functional neurological symptoms, Somatoform dissociation, Conversion, Dissociative movement and sensibility disorders, Adverse childhood experiences, Life events, Alexithymia, Suppression, Emotion regulation, Building block effect; 150